대장암에서 CD31과 D2-40 발현에 의한 혈관성 및 림프관성 미세혈관 밀도 측정 - 윤상인(Sang In Youn); 김범규(Beom Gyu Kim); 차성재(Seong Jae Cha); 박성준(Sung Jun Park); 장인택(In Taek Chang); 박성일(Sung Il Park); 이태진(Tae Jin Lee) (Annals of surgical treatment and research, 2007)
Purpose: Angiogenesis and lymphangiogenesis play important roles in the growth, progression and metastasis of colon cancer. We performed this study in order to investigate the significance of the CD31 and D2-40 expressions as prognostic factors in colon cancer. Methods: The angiogenic and lymphagiogenic microvessel density was assessed by immunohistochemical staining of CD31 and D2-40 on samples that were resected from 66 patients with colorectal cancer. Results: Strong correlation was observed between the CD31 microvessel density and being positive for having tumor emboli and lymph node metastasis (P=0.001, P=0.003). The D2-40 lymphatic vessel density was correlated with being positive for having tumor emboli (P=0.0001), the depth of invasion (P=0.0001), lymph node metastasis (P= 0.0001) and the cancer stage (P=0.0001). The D2-40 lymphatic vessel density was also correlated with the CD31 count (P=0.003). Conclusion: These results suggested that the CD31 and D2-40 expressions are useful predictors of lymph node metastasis and they are prognostic factors for colon cancer. (J Korean Surg Soc 2007;73:315-320) KCI Citation Count: 1